2000
DOI: 10.1007/s004390000257
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mutation analysis of the gene encoding DNA fragmentation factor 40 (caspase-activated nuclease), a candidate neuroblastoma tumour suppressor gene

Abstract: We have characterised the DFFB gene, encoding the active subunit of the apoptotic nuclease DNA fragmentation factor (DFF40). DFFB maps to 1p36, near the imprinted putative tumour suppressor gene TP73. The DFFA gene (encoding the inhibitory DFF45 subunit) also maps to 1p36.2-36.3, and we show by FISH that DFFB lies distal to DFFA. We have also mapped a processed DFFB pseudogene to chromosome 9. DFFB itself has seven coding exons spanning 10 kb. Exhaustive mutation screening of 41 neuroblastomas and other tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…However, these studies have not identified a consistent region of deletion. Furthermore, these and other studies have proposed over 20 genes within these regions as candidate neuroblastoma tumor suppressors, none of which have yet been proven to play a significant causative role in neuroblastoma tumor development (Ejeskar et al, 2000;Judson et al, 2000;De Toledo et al, 2001;Huang et al, 2001;Abel et al, 2002;Cerignoli et al, 2002;Krona et al, 2003;Thompson et al, 2003;Mathysen et al, 2004). Our current work was designed to determine the location and extent of 1p deletion in a very large primary tumor cohort by extensive genotyping, sequencing, gene identification, and transcript characterization.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have not identified a consistent region of deletion. Furthermore, these and other studies have proposed over 20 genes within these regions as candidate neuroblastoma tumor suppressors, none of which have yet been proven to play a significant causative role in neuroblastoma tumor development (Ejeskar et al, 2000;Judson et al, 2000;De Toledo et al, 2001;Huang et al, 2001;Abel et al, 2002;Cerignoli et al, 2002;Krona et al, 2003;Thompson et al, 2003;Mathysen et al, 2004). Our current work was designed to determine the location and extent of 1p deletion in a very large primary tumor cohort by extensive genotyping, sequencing, gene identification, and transcript characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Upon apoptosis induction, caspase cleaves the inhibitor and releases DFFB from the complex to enter into nuclei to degrade chromosomal DNA (Nagase et al, 2003). No somatic mutations of DFFB were detected in 41 neuroblastomas examined (Judson et al, 2000). However, aberrant DFFB transcripts resulting from splicing have been reported in hepatocellular carcinoma (Hsieh et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This gene is located at 1p36.3 and was shown to be a monoallelically expressed gene (reviewed in [152]) with maternal expression. Information about the imprinting of TP73 gene in cancers is still limited and contradictory [153].…”
Section: Predict Imprinted Genes and Bladder Cancermentioning
confidence: 99%